VITAMIN C PREVENTS STRESS INDUCED CARDIOMYOPATHY IN PRENATAL NOISE EXPOSED RODENTS - Winnie Nirmala Santosa; Viskasari P. Kalajanti; Ni Wajan Tirthaningsih (Universitas Muhammadiyah Sumatera Utara, 2019)
Potency of oral vitamin C to prevent cardiomyopathy in prenatal noise exposed newborn Wistar rats was studied by comparing the cardiomyocyte numbers and the extracellular matrix expressions (ECM) to controls. Twenty-four newborns (NR) of 32 pregnant mothers were divided equally into 4 groups: K1 (distilled water [DW]), K2 (150 mg/kg of BW oral vitamin C once daily [VC]), P1 (4 hours daily of white noise at 95 dB [WN]+DW), and P2 (WN+VC). VC and WN were given from D1 till birth and from D15 till birth, respectively. The hearts of NR were harvested, and processed for histology slides (2 midsagittal 4 μ cut slides/ animal) stained with hematoxyllin-eosin and Masson trichrome for the cardiomyocytes and ECM quantification at the ventricles using Image Raster 3.0 and ImageJ, respectively. Pictures from 8 visual fields/ slide were taken and analyzed in duplicate (400x magnifications under a light microscope). Data were analyzed using SPSS 17; significance level of p<0.05. In P1, the cardiomyocite cell numbers was significantly lowest (p<0.001); whilst the ECM was significantly highest than K1, K2, P2 (p<0.001 and p<0.005, respectively). Here, vitamin C could prevent the adverse effect of prenatal noise exposures in the ventricle myocardium of newborn rats.Keywords: cardiomyopathy, hypertrophy, prenatal noise, vitamin C